2018
DOI: 10.1016/j.apsusc.2018.02.116
|View full text |Cite
|
Sign up to set email alerts
|

Using sub-micron silver-nanoparticle based films to counter biofilm formation by Gram-negative bacteria

Abstract: Composite films comprised of silver nanoparticles (AgNPs) grown using a low-cost straightforward chemical bath based method have been deposited on glass microscope slides to investigate their potential as a sacrificial antibacterial coating. The as-deposited films have been characterised using scanning electron microscopy (SEM) and optical profilometry. These suggested that the films were relatively uniform in coverage. Chemical composition of the AgNP films has been studied by using xray photoelectron spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…These few examples suggest that the combination of different elements into the coating is likely needed to provide a wide spectrum of anti-biofilm activity, though the role of the coating roughness has not been explored in detail. On the other hand, investigations into the effect of individual NPs on the biofilm disruption has been obtained for Au [36,102], Ag [103], Mg [104], ZnO [42,102,105], CuO [102,106], CeO [102], Fe 3 O 4 [107], YF [108] and TiO 2 [101], indicating that smaller NPs with high surface to volume ratio have a remarkable effect on biofilm destruction [98].…”
Section: Antibiofilm Activitymentioning
confidence: 99%
“…These few examples suggest that the combination of different elements into the coating is likely needed to provide a wide spectrum of anti-biofilm activity, though the role of the coating roughness has not been explored in detail. On the other hand, investigations into the effect of individual NPs on the biofilm disruption has been obtained for Au [36,102], Ag [103], Mg [104], ZnO [42,102,105], CuO [102,106], CeO [102], Fe 3 O 4 [107], YF [108] and TiO 2 [101], indicating that smaller NPs with high surface to volume ratio have a remarkable effect on biofilm destruction [98].…”
Section: Antibiofilm Activitymentioning
confidence: 99%
“…It is well reported that silver has anti-biofilm properties with most studies demonstrating the activity of AgNPs, AgNO3 or AgSD [241,243,[410][411][412]442], and more recently silver oxynitrate (Ag7NO11) [443]. As expected, both apt-AgNC and apt-AgiM treatments had anti-biofilm properties with inhibition of the growth of planktonic cells shed from the biofilm and disruption of the biofilm biomass relative to the untreated control.…”
Section: Anti-biofilm Propertiessupporting
confidence: 63%
“…The field of antimicrobial AgNPs is vast and continually expanding. AgNPs have been implicated in the prevention, detachment and killing of bacterial biofilms, P. aeruginosa in particular [226,[241][242][243][244][245][246], as well as eliciting strong synergistic effects when used in combination with other antibacterials [247] such as tobramycin [248],…”
Section: Silver Nanoparticlesmentioning
confidence: 99%
“…Yu et al, (2018) studied the silver nanoparticle decorated quercetin nanoparticles against biofilm formed by Escherichia coli during mastitis and was proved to have stronger antibiofilm activity. Gillett et al, (2018) studied chemical composition of Ag-NP using X-ray photoelectron spectroscopy and 10.6 nm sized particle was tested against E. coli biofilm formation and found to be effective in slowing initial biofilm formation. Sambalova et al, (2018) found that biopolymer fraction of biofilm organic matrix can reduce ionic silver (Ag) and thus stabilize the formed nano silver and found that the Ag particle biopolymer interface is dominated by carboxylate functional groups.…”
Section: Silver Nano Particlesmentioning
confidence: 99%